Method for producing active metal paste, method for producing ceramic circuit board, method for producing semiconductor device, active metal paste, ceramic circuit board and semiconductor device

By using the premix and rotation and kneading process in the manufacturing of ceramic circuit substrates, the problem of uniform mixing in improving the bonding strength and thermal cycling characteristics of ceramic circuit substrates is solved, and cost reduction and performance improvement are achieved.

CN119173349APending Publication Date: 2024-12-20SPECIAL CERAMIC MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380038547.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-01-17
Filing Date
2023-12-13
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

In the prior art, when improving the bonding strength and thermal cycling characteristics of ceramic circuit substrates, it is difficult to uniformly mix the active metal brazing components, resulting in problems of increasing costs and prolonging mixing time.

Method used

The resin is dissolved in an organic solvent and mixed with the metal powder by a pre-mixing process, and then the active metal paste is generated through the kneading process of rotation and revolution, and the metal powder is dispersed to achieve more uniform mixing.

Benefits of technology

A more uniform mixing of active metal paste is achieved, reducing costs, and improving the bonding strength and thermal cycling characteristics of the ceramic circuit substrate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119173349A_ABST
    Figure CN119173349A_ABST
Patent Text Reader

Abstract

A method for producing an active metal paste according to an embodiment includes a premixing step and a kneading step. In the pre-mixing step, a binder obtained by dissolving a resin in an organic solvent is mixed with a metal powder containing copper and an active metal, and a mixture containing 60-95% by mass of the metal powder is produced. In the kneading step, rotation and revolution are applied to the mixture to produce an active metal paste.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments generally relate to a method for producing an active metal paste, a method for producing a ceramic circuit substrate, a method for producing a semiconductor device, an active metal paste, a ceramic circuit substrate, and a semiconductor device. Background Art

[0002] Ceramic circuit substrates are used in semiconductor devices equipped with semiconductor elements such as power elements. The ceramic substrate and the metal circuit portion are bonded to each other via a bonding layer using an active metal brazing material or the like. This improves the bonding strength and thermal cycle characteristics. With the improvement in reliability, ceramic circuit substrates are used in automobiles (including electric vehicles), electric railway vehicles, solar power generation equipment, industrial machinery converters, and the like. In semiconductor devices such as power modules, semiconductor elements are installed in the circuit portion. In addition, in order to conduct the semiconductor element, a wire bonding portion or a metal terminal is sometimes bonded. In the manufacture of semiconductor devices, semiconductor elements, wire bonding portions, metal terminals, and the like are bonded to the circuit portion.

[0003] As a method for forming a bonding layer of a ceramic circuit substrate, a method of pasting an active metal brazing material and printing it on a ceramic substrate is disclosed (Patent Document 1). According to Patent Document 1, the mixing process of the mixed brazing component powders is carried out for more than 10 hours, and a binder and a solvent are mixed in the mixed powder to adjust the brazing paste. The mixing process of the mixed powder and the binder is carried out for more than 10 hours. In the bonding layer using the paste of Patent Document 1, the distribution of Ag (silver) is controlled to suppress the difference in etching effect. It is disclosed that controlling the size of the protruding portion of the bonding portion obtained by etching is related to the improvement of the temperature cycle test (TCT) characteristics.

[0004] As a method for producing a paste, a method for mechanically dispersing a kneaded product is disclosed (Patent Document 2). According to Patent Document 2, for mechanical dispersing, ultrasonic dispersion, disperser, three-roll mill, ball mill, bead mill, biaxial kneader, self-revolving mixer, etc. can be listed. In Patent Document 2, ultrasonic dispersion and three-roll are listed as specific embodiments.

[0005] Furthermore, among the methods for producing a paste, a method for producing a paste using a self-revolving mixer is disclosed (Patent Document 3). According to Patent Document 3, a silver paste is prepared by kneading silver powder, terpineol, and resin using a self-revolving mixer at a centrifugal force of 420G.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. 2022 / 085654

[0009] Patent Document 2: International Publication No. 2012 / 070262

[0010] Patent Document 3: Japanese Patent No. 5790433 Summary of the invention

[0011] Problems to be solved by the invention

[0012] With the increase in the reliability of semiconductor substrates that require the use of ceramic circuit substrates, the issues arising from improving the bonding strength and thermal cycle characteristics of ceramic circuit substrates have become apparent. In order to improve the characteristics, it is required to use a solder corresponding to the purpose, and to mix these solder components uniformly and efficiently to form a paste. The metal material used in the solder has different shapes and densities of powder depending on the type. Furthermore, the metal material also needs to consider mixing with the solvent and resin components used for pasting. Although the paste components can be uniformly mixed by extending the mixing time, the operating time is also extended in proportion to it, and the cost increases.

[0013] In order to solve such problems, embodiments of the present invention provide a method for producing an active metal paste that can suppress an increase in cost and knead the paste more uniformly, and a method for producing a ceramic circuit board and a semiconductor device using the active metal paste. In addition, embodiments of the present invention provide an active metal paste that is kneaded more uniformly, and a ceramic circuit board and a semiconductor device using the same.

[0014] Means for solving problems

[0015] The method for producing an active metal paste according to the embodiment includes a premixing step and a kneading step. In the premixing step, a binder obtained by dissolving a resin in an organic solvent is mixed with metal powders containing copper and an active metal to generate a mixture containing 60 to 95% by mass of the metal powders. In the kneading step, the mixture is subjected to rotation and revolution to generate an active metal paste. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a side view showing an example of the ceramic circuit board according to the embodiment.

[0017] Figure 2 It is a process flow chart showing an example of a method for producing an active metal paste according to an embodiment.

[0018] Figure 3 It is a schematic diagram showing an example of a kneading process of the active metal paste according to the embodiment.

[0019] Figure 4 It is a cross-sectional view showing an example of a manufacturing process of the ceramic circuit board according to the embodiment.

[0020] Figure 5 It is a side view showing an example of a semiconductor device according to an embodiment. DETAILED DESCRIPTION

[0021] The method for manufacturing an active metal paste according to the embodiment is a method for manufacturing an active metal paste containing 60 to 95% by mass of a metal powder containing copper and at least one active metal in the paste. In the manufacturing method, there are a pre-mixing step of mixing a binder obtained by dissolving a resin in an organic solvent with the above-mentioned metal powder, and a kneading step of kneading the pre-mixed paste. In addition, in the above-mentioned kneading step, the pre-mixed paste is subjected to a kneading treatment of applying rotation and revolution. The active metal paste is used for the manufacture of a ceramic circuit substrate.

[0022] Figure 1 It is a cross-sectional view showing an example of the ceramic circuit board according to the embodiment. Figure 1 In the figure, 1 is a ceramic circuit substrate. 2 is a ceramic substrate. 3 is a metal circuit. 4 is a bonding layer. The metal circuit 3 is bonded to the ceramic substrate 2 via the bonding layer 4. Figure 1 In the example of , three metal circuits 3 are respectively bonded to the upper surface of the ceramic substrate 2 via three bonding layers 4. One metal circuit 3 is bonded to the lower surface of the ceramic substrate 2. The metal circuit 3 on the lower surface may function as a heat sink instead of a circuit. The embodiment is not limited to the illustrated example. For example, one, two, or four or more metal circuits 3 may be bonded to the upper surface of the ceramic substrate 2.

[0023] The ceramic substrate 2 is preferably any one of a silicon nitride substrate, an aluminum nitride substrate and an aluminum oxide substrate. An alumina zirconia substrate can be listed as one type of aluminum oxide substrate. Alumina zirconia is a sintered body in which 20 to 80% by mass of aluminum oxide is used and the remainder is zirconium oxide. The three-point bending strength of each of the aluminum nitride substrate and the aluminum oxide substrate is about 300 to 450 MPa. The strength of the alumina zirconia substrate is about 550 MPa. The three-point bending strength of the silicon nitride substrate is above 600 MPa, and can be further increased to above 700 MPa. The thermal conductivity of the silicon nitride substrate is above 50 W / (m·K), and can be further increased to above 80 W / (m·K). In recent years, in particular, there are silicon nitride substrates that have both high strength and high thermal conductivity. Since the silicon nitride substrate has high strength, it can be thinned, which can further improve the heat dissipation. In order to improve the heat dissipation, the thickness of the silicon nitride substrate is preferably less than 0.635 mm, and more preferably less than 0.3 mm. The lower limit of the thickness is not particularly limited, but is preferably greater than 0.1 mm. This is to ensure the electrical insulation of the silicon nitride substrate. The thickness here refers to the size of the ceramic substrate 2 in the direction connecting the upper surface and the lower surface of the ceramic substrate 2. These ceramic substrates 2 can be single plates or have three-dimensional structures such as multilayer structures. The thickness of the ceramic substrate 2 is not particularly limited. By thinning the ceramic circuit substrate and thickening the metal circuit, the heat dissipation is improved.

[0024] The metal used in the metal circuit 3 is copper, copper alloy, etc. Copper and copper alloy have high electrical conductivity and are suitable for electrical circuits. In addition, copper and copper alloy have high thermal conductivity, so they are also excellent in heat dissipation from semiconductor elements mounted on the metal circuit 3. For example, the metal circuit 3 is made of copper or copper alloy except for impurities.

[0025] The ceramic substrate 2 and the metal circuit 3 are preferably bonded via a bonding layer 4. The bonding layer 4 preferably includes one or more active metals selected from the group consisting of copper (Cu) and silver (Ag) and one or more active metals selected from the group consisting of titanium (Ti), zirconium (Zr), hafnium (Hf) and niobium (Nb). The bonding layer 4 may further include one or more active metals selected from the group consisting of tin (Sn), indium (In), zinc (Zn), magnesium (Mg) and aluminum (Al). In addition, the bonding layer 4 may also include inorganic substances other than metals such as silicon (Si) or carbon (C). When the metal circuit 3 is copper or a copper alloy, the bonding layer 4 preferably includes Cu and Ti.

[0026] Figure 2 1 is a process flow chart showing an example of a method for producing an active metal paste according to an embodiment. The production method according to the embodiment includes a binder preparation step, a premixing step, and a kneading step.

[0027] First, an organic solvent, resin powder, and metal powder are prepared. The organic solvent is not particularly limited as long as it is a solvent that is burned out in the drying process and the bonding process. As a preferred example of the organic solvent, terpineol, butyl carbitol, etc. can be listed. The resin is not particularly limited as long as it is a resin that is burned out in the drying process and the bonding process. As a preferred example of the resin, ethyl cellulose, polyvinyl butyral, acrylic resin, etc. can be listed.

[0028] The metal powder contains one or more active metals selected from the group consisting of Cu and Ag and one or more active metals selected from the group consisting of Ti, Zr, Hf and Nb. The metal powder may further contain metal components such as Sn, In, Zn, Al, and Mg. The metal powder may further contain inorganic components such as C and Si. For example, in the case where the metal powder contains Cu and Ti, the content of Cu contained in the metal powder is preferably 50% by mass or more, the content of Ti is 4% by mass or more and 30% by mass or more, the content of one or two selected from Sn or In is 5% by mass or more and 45% by mass or less, and the content of C is 0% by mass or more and 2% by mass or less. In the case where the metal powder contains Ag, Cu and Ti, the content of Ag contained in the metal powder is preferably 20% by mass or more and 60% by mass or less, the content of Cu is 15% by mass or more and 40% by mass or less, the content of Ti is 1% by mass or more and 15% by mass or less, and the content of one or two selected from Sn or In is 5% by mass or more and 25% by mass or less. If necessary, one or more selected from the group consisting of Al, Si, and Mg may be added in an amount within a range of 1 to 15 mass %.

[0029] In the binder preparation process, the resin is dissolved in an organic solvent to prepare a binder. In addition to the resin and the organic solvent, a dispersant or a surfactant may be added as needed to help disperse and prevent aggregation. It should be noted that a commercially available binder obtained by dissolving the resin in an organic solvent may be prepared to omit the binder preparation process.

[0030] Next, a premixing step is performed to mix the metal powder with the prepared binder. In the premixing, the binder and the metal powder are mixed and fused using a stirrer or a pounder. Since the metal powder is sometimes not mixed and remains, the mixing is performed in a manner that the metal powder does not coagulate visually. Through the premixing step, a mixture of the binder and the metal powder is obtained.

[0031] Next, a kneading step is performed to convert the mixture into a paste. The kneading step allows the metal powder to be more uniformly dispersed in the mixture, and a paste suitable for printing can be obtained.

[0032] Figure 3Schematic diagram showing an example of a kneading process of the active metal paste according to the embodiment. Figure 3 5 is a mixing container in which a mixture of an adhesive and metal powder is placed. The mixing container 5 rotates around the axis AX1. In addition, the mixing container 5 revolves around the axis AX2. The axis AX1 is inclined relative to the axis AX2. For example, the axis AX1 is inclined relative to the vertical direction. The axis AX2 is parallel to the vertical direction. The angle θ between the axis AX1 and the axis AX2 is preferably greater than 25 degrees and less than 50 degrees, and more preferably greater than 30 degrees and less than 45 degrees. The rotation direction RD1 of the mixing container 5 when observed from the direction D1 parallel to the axis AX1 is opposite to the rotation direction RD2 of the mixing container 5 when observed from the direction D2 parallel to the axis AX2. In the illustrated example, when observed from the direction D1, the mixing container 5 rotates to the left (counterclockwise). In addition, when observed from the direction D2, the mixing container 5 revolves to the right (clockwise). By the mixing container 5 revolving, a force moving in the centrifugal direction relative to the mixture of the adhesive and the metal powder acts, and the mixture is degassed. Furthermore, the kneading container 5 is rotated, and the mixture is stirred by convection.

[0033] In the kneading process, in order to efficiently carry out kneading, it is preferred to change the kneading conditions and separate the steps. The kneading process includes 1st kneading, 2nd kneading and 3rd kneading. In the 1st kneading, kneading is essentially carried out only by revolution. In the 2nd kneading, kneading is carried out by revolution and rotation. The rotation speed of the revolution in the 2nd kneading is less than the rotation speed of the revolution in the 1st kneading. The rotation speed of the rotation in the 2nd kneading is less than the rotation speed of the revolution in the 2nd kneading. In the 3rd kneading, kneading is carried out by revolution and rotation. The rotation speed of the revolution in the 3rd kneading is greater than the rotation speed of the revolution in the 2nd kneading. The rotation speed of the rotation in the 3rd kneading is less than the rotation speed of the revolution in the 3rd kneading. In the 1st kneading, the kneading container 5 can also rotate, but the rotation speed of the rotation is preferably sufficiently less than the rotation speed of the rotation in the 2nd kneading or the 3rd kneading. By processing in stages from the 1st kneading to the 3rd kneading, the mixture can be efficiently kneaded.

[0034] In the first kneading, the mixture is kneaded for a preset time by revolution while maintaining the rotation speed. In the second and third kneading, the mixture is kneaded for a preset time by revolution and rotation while maintaining the rotation speed of each.

[0035] In the first kneading, the degassing of the mixture is promoted by performing kneading that is essentially only revolution. In the mixture, the atmosphere brought in during the manufacturing process exists as bubbles. If the paste in the state where bubbles remain is printed, defects such as pores may occur. Therefore, it is preferred to remove bubbles as much as possible. If the mixture is stirred in a state where the degassing is not fully performed, the bubbles in the mixture are finely cut off. In appearance, the mixture is degassed and the bubbles are difficult to be confirmed, but only the minor defects are dispersed, which is not preferred. In order to fully degas, the centrifugal acceleration of the first kneading is preferably more than 80% of the centrifugal acceleration of the third kneading. If the centrifugal acceleration is lower than 80%, it is possible that the mixture cannot be fully degassed. The centrifugal acceleration of the first kneading is more preferably more than 85% of the centrifugal acceleration of the third kneading, and most preferably more than 90% of the centrifugal acceleration of the third kneading. On the other hand, if the centrifugal acceleration of the first kneading is too large, it is possible that minor defects are dispersed and remain as described above. Therefore, the centrifugal acceleration of the first kneading is preferably 100% or less of the centrifugal acceleration of the third kneading, and more preferably 95% or less of the centrifugal acceleration of the third kneading.

[0036] The time for one kneading is preferably at least 10% of the total kneading time. If the kneading time is less than 10%, the mixture may not be fully degassed. The longer the time for one kneading is, the more the mixture is degassed. However, if the time for one kneading is extended beyond the necessary time, the overall kneading process will be longer and the temperature of the mixture will rise. As a result, the kneading process may affect the physical properties of the paste, such as viscosity. Therefore, the time for one kneading is preferably less than 20% of the total kneading time, and more preferably less than 15%.

[0037] In the second kneading, the deaerated mixture is stirred by rotation by performing rotation in addition to revolution. By rotating the mixture greatly, the metal powders are stirred with each other and the metal powders and the binder are stirred, and the metal powders are dispersed more evenly. The purpose of the second kneading is to stir the entire mixture. Therefore, in the second kneading, kneading is performed by revolution with a rotation speed less than that of the first kneading and rotation with a rotation speed less than that of the revolution. By reducing the rotation speed of the revolution compared to the first kneading, the force that moves the mixture in the centrifugal direction is suppressed. By suppressing the force that moves in the centrifugal direction, although the deaeration effect of the mixture is reduced, it becomes easy to produce the flow of the material. In addition, by performing rotation with a rotation speed less than that of the revolution, the stirring of the mixture is promoted. The mixture contains metal powder and binder. If the metal powders are not stirred with each other and the metal powders and the binder are not stirred sufficiently, a paste in which the metal powders are evenly dispersed in the binder cannot be obtained. Therefore, it is preferred to stir the metal powder in the binder as much as possible. If the paste is formed without sufficient stirring, there is a possibility that a paste containing no metal powder and only the binder portion is present, or a paste containing a portion where the metal component is concentrated is obtained, which is not preferable.

[0038] In order to achieve sufficient stirring, the centrifugal acceleration of the second kneading is preferably 50% or more of the centrifugal acceleration of the third kneading. If the centrifugal acceleration is lower than 50%, the metal powder may not be sufficiently stirred. The centrifugal acceleration of the second kneading is more preferably 60% or more of the centrifugal acceleration of the third kneading, and most preferably 70% or more of the centrifugal acceleration of the third kneading. On the other hand, if the centrifugal acceleration of the second kneading is too large, it is possible to paste the powder without stirring as described above. Therefore, the centrifugal acceleration of the second kneading is preferably 90% or less of the centrifugal acceleration of the third kneading, and more preferably 80% or less of the centrifugal acceleration of the third kneading.

[0039] The time of the second kneading is preferably at least 10% of the total kneading time. If the kneading time is less than 10%, the metal powder may not be fully stirred. The longer the time of the second kneading is, the more the metal powder can be stirred. However, if the time of the second kneading is extended beyond the necessary time, the overall kneading time becomes longer and the temperature of the mixture rises. As a result, the kneading process may affect the physical properties such as the viscosity of the paste. Therefore, the time of the second kneading is preferably less than 20% of the total kneading time, and more preferably less than 15%.

[0040] In the third kneading, a large stirring is performed by applying a larger revolution and rotation to the kneaded material stirred by the second kneading. The stirring by applying a shear force to the mixture is performed by a rotation speed greater than the revolution of the second kneading and a rotation speed less than the revolution. The stirring by applying a shear force promotes the paste-forming of the mixture. The force applied to the mixture by the third kneading is preferably greater than the force applied to the mixture by the first kneading, and greater than the force applied to the mixture by the second kneading. That is, the centrifugal acceleration in the third kneading is preferably greater than the centrifugal acceleration of the first kneading, and greater than the centrifugal acceleration of the second kneading. In order to make the centrifugal acceleration of the third kneading greater than the first kneading and the second kneading, it is preferred that the rotation speed of the revolution in the third kneading is greater than the rotation speed of the revolution in the first kneading and the second kneading, and the rotation speed of the rotation in the third kneading is greater than the rotation speed of the rotation in the first kneading and the second kneading. The centrifugal acceleration can be increased by increasing the rotation speed of only one of the revolution or rotation in the third kneading compared with the first and second kneading. However, the revolution centrifugal force or the rotation centrifugal force may become too large, which may cause excessive load on the device or the mixture.

[0041] It is also considered to omit the second kneading and proceed directly from the first kneading to the third kneading, but in the case of insufficient premixing or insufficient stirring in the third kneading, it is possible to produce a paste in which the metal powder is not fully dispersed. Therefore, the kneading process preferably includes the three steps of the first kneading, the second kneading and the third kneading. As long as the kneading process includes the first to third kneading, other kneading steps can also be set between the first kneading and the second kneading, between the second kneading and the third kneading, or after the third kneading. However, as mentioned above, the increase in the overall kneading time will cause the temperature of the mixture to rise. Therefore, when setting other steps, the time of the step is preferably short.

[0042] Through the above process, an active metal paste can be obtained. The paste completed by kneading is printed on a ceramic substrate. The printing thickness of the paste is preferably 15 to 40 μm. If the printing thickness is less than 15 μm, the thickness of the active metal brazing material layer may be uneven, and the bonding strength may be reduced. On the other hand, even if the printing thickness exceeds 40 μm, the effect of bonding strength will not be improved, thus leading to an increase in cost. The paste is printed on the end surface of the ceramic component with uniform thickness by screen printing or the like. If the printing thickness is uneven, the active metal brazing material becomes excessive in the thick part, forming brazing material accumulation and generating cracks caused by thermal stress. In the thin part, a portion with reduced strength is generated due to the lack of active metal brazing material. Therefore, for the printed paste, the difference between the thickness of the thickest part and the thickness of the thinnest part is preferably less than 10 μm, and more preferably less than 5 μm.

[0043] Figure 4 (A)~ Figure 4(E) is a cross-sectional view showing an example of a manufacturing process of the ceramic circuit board according to the embodiment. Figure 4 (A) shows the ceramic substrate 2 before printing the active metal paste 6. Figure 4 As shown in (B), the active metal paste 6 is printed on the upper surface of the ceramic substrate 2 and dried. In the example shown in the figure, the active metal paste 6 is selectively printed only in the area where the metal circuit is to be provided later. Figure 4 As shown in (C), the active metal paste 6 is printed on the lower surface of the ceramic substrate 2 and dried. Figure 4 As shown in (D), a metal plate 7 is placed on the surface of the dried active metal paste 6 to bond it. The active metal paste 6 melts and solidifies to form a bonding layer 4. Figure 4 As shown in (E), the metal plate 7 is processed into the shape of a metal circuit by etching or the like, thereby forming the metal circuit 3. Through the above steps, the ceramic circuit substrate 1 including the ceramic substrate 2 and the metal circuit 3 is manufactured.

[0044] exist Figure 4 In the process shown in (B), the active metal paste 6 may be printed on the upper surface of the ceramic substrate 2 in a wider range than the metal circuit 3. In this case, after a part of the metal plate 7 is etched, a part of the bonding layer 4 is etched. In addition, it is also possible to prepare pre-processed metal circuits 3 and arrange these metal circuits 3 on the active metal paste 6. In this case, Figure 4 The etching step shown in (D) is omitted.

[0045] A metal thin film may also be provided on the surface of the metal circuit 3 of the ceramic circuit substrate 1. The metal thin film has one selected from the group consisting of Ni (nickel), Ag (silver) and Au (gold) as a main component. Here, "main component" refers to a component containing 50% or more. The metal thin film is a plated film, a sputtered film, etc. By providing a metal thin film, corrosion resistance, wettability of solder, etc. can be improved.

[0046] Figure 5 (A) and Figure 5 (B) is a side view showing an example of a semiconductor device according to the embodiment. The ceramic circuit substrate 1 according to the embodiment is suitable for a semiconductor device. In the semiconductor device, a semiconductor element is mounted via a bonding layer in a metal circuit 3. Figure 5 In (A), 1 is a ceramic circuit substrate. 8 is a bonding layer. 9 is a semiconductor element. 10 is a semiconductor device. 11 is a wire bonding portion. 12 is a lead frame. Figure 5 In (B), 13 is a molding resin. Figure 5 (B) means Figure 5The semiconductor device 10 shown in (A) is in a state covered with a molding resin 13 .

[0047] like Figure 5 As shown in (A), a semiconductor element 9 is mounted on the metal circuit 3 of the ceramic circuit substrate 1 via a bonding layer 8. Adjacent metal circuits 3 are connected to each other through wire bonding portions 11. The semiconductor device 10 involved in the embodiment is not limited to such a structure. For example, a plurality of semiconductor elements 9 and wire bonding portions 11 may be respectively provided on the metal circuit 3 on the upper surface. In addition, semiconductor elements, wire bonding portions, etc. may be bonded to the metal circuit 3 on the lower surface as required. In the ceramic circuit substrate 1, metal terminals such as lead frames may also be bonded. For the bonding layer 8 for bonding the semiconductor element 9, solder, brazing material, etc. are used. The solder is preferably a lead-free solder. "Solder" refers to a bonding material having a melting point of 450°C or less. "Brass" refers to a bonding material having a melting point of more than 450°C. A bonding material having a melting point of 500°C or more is called a high-temperature solder. As a high-temperature solder, a material having Ag as a main component can be listed.

[0048] As the miniaturization of semiconductor elements 9 progresses, on the other hand, the heat dissipation from semiconductor elements 9 is increasing. Therefore, the ceramic circuit substrate 1 equipped with semiconductor elements 9 is required to improve heat dissipation. In order to improve the performance of the semiconductor device 10 (semiconductor module), multiple semiconductor elements 9 can be mounted on the ceramic circuit substrate 1. If a semiconductor element 9 exceeds the intrinsic temperature of the element, the resistance changes to a negative temperature coefficient. Along with this, thermal runaway occurs in which electric power flows in a concentrated manner, causing the semiconductor device 10 to be destroyed instantly. Therefore, it is very effective to improve the reliability of the connection between the semiconductor element 9 and the metal circuit 3. In addition, the semiconductor device 10 involved in the embodiment can be used for PCU, IGBT, and IPM modules. PCU, IGBT, and IPM modules are used in converters for automobiles (including electric vehicles), electric railway vehicles, industrial machinery, and air conditioners. With regard to automobiles, the popularization of electric vehicles is progressing. The higher the reliability of the semiconductor device, the higher the safety of the automobile can be. The same is true for electric railway vehicles, industrial equipment, etc.

[0049] A specific example of the method for producing the ceramic circuit board 1 according to the embodiment will be described. As long as the ceramic circuit board 1 has the above-mentioned configuration, the method for producing the ceramic circuit board 1 is not particularly limited. Here, an example of a method for obtaining the ceramic circuit board 1 with a high yield is given.

[0050] First, prepare a ceramic substrate 2 and a metal plate 7. The ceramic substrate 2 is preferably one selected from a silicon nitride substrate, an aluminum nitride substrate, and an aluminum oxide substrate. In particular, if the overall heat dissipation of the ceramic circuit substrate 1 is considered, the ceramic substrate 2 is preferably a silicon nitride substrate having a thermal conductivity of 50 W / (m·K) or more and a three-point bending strength of 600 MPa or more. The metal plate 7 is preferably formed of one selected from copper or a copper alloy. In the case where the metal circuit 3 provided on the upper surface of the ceramic substrate 2 is connected to the metal circuit 3 provided on the lower surface through a through hole, a ceramic substrate 2 having a through hole is prepared. In the case where a through hole is provided in the ceramic substrate 2, the through hole can also be provided in advance at the stage of the formed body. In addition, a through hole can also be provided in the ceramic substrate 2 (ceramic sintered body). The through hole is provided by laser processing, cutting processing, etc. As cutting processing, hole opening processing using a drill bit, etc. can be listed.

[0051] The ceramic substrate 2 is preferably joined to a copper plate or a copper alloy plate by an active metal bonding method. In the active metal bonding method, an active metal brazing filler metal formed by mixing active metals such as Ti with Cu is used. As active metal brazing filler metals, a mixture of Ti and Cu, a mixture of Ti, Ag and Cu, etc. can be listed. For example, in a mixture of Ti and Cu, the content of Cu in the inorganic component contained in the mixture is more than 50 mass %, the content of Ti is more than 4 mass % and more than 30 mass %, the content of one or two selected from Sn or In is more than 5 mass % and less than 45 mass %, and the content of C is more than 0 mass % and less than 2 mass %. "Inorganic component" refers to components other than organic components contained in organic solvents, resins, etc., and is inorganic components other than metal elements such as Ag, Cu, active metals, and metals such as Si and C contained in metal powder. In a mixture of Ti, Ag and Cu, the content of Ag in the inorganic component contained in the mixture is 20 mass % or more and 60 mass % or less, the content of Cu is 15 mass % or more and 40 mass % or less, the content of Ti is 1 mass % or more and 15 mass % or less, and the content of one or two selected from Sn or In is 5 mass % or more and 25 mass % or less. In addition, as required, one or more selected from the group consisting of Al, Si and Mg may be added in the range of 1 to 15 mass %.

[0052] Next, the active metal brazing filler metal is made into paste. Prepare metal powders of the metal mass ratio used in the active metal brazing filler metal paste. If the metal powder is too fine, the metal powder is easy to agglomerate and difficult to disperse evenly. In addition, if the metal powder is too coarse, it is difficult for the metal components to mix with each other when they are melted by joining. Therefore, if it is the above composition, the average particle size of the metal powder is preferably 1 to 5 μm. If the proportion of metal powder in the paste is too small, when the organic component evaporates by drying and heating for joining, the brazing filler metal component required for joining cannot be obtained. In addition, if the proportion of metal powder is too large, the viscosity required for printing cannot be obtained as a paste. Therefore, although the overall specific gravity may vary according to the mixing ratio of the active metal brazing filler metal, the metal powder is preferably contained in the paste at 60 to 95 mass%.

[0053] Next, the binder of the mixed metal powder is blended. The binder is made by dissolving the resin component in an organic solvent. As a preferred example of the resin used in the binder blending, ethyl cellulose can be cited. In addition, as a preferred example of the organic solvent, terpineol can be cited. If there are more resins and less organic solvents in the binder, the viscosity of the binder becomes higher, and the binder becomes difficult to mix with the metal powder. If there are less resins and more organic solvents in the binder, the viscosity of the binder becomes lower, and a paste suitable for printing cannot be obtained. Therefore, the amount of resin contained in the binder is preferably 5 to 15% by mass. In addition to the resin and the organic solvent, in order to help disperse and prevent aggregation, dispersants and surfactants such as sodium lauroyl sarcosinate and oleic acid can also be added as needed. The amount of dispersant or surfactant added is 0.1 to 5% by mass. When the resin is difficult to dissolve in the organic solvent, stirring with a stirrer or mixer, placing it in a closed container and stirring it by rotating a pot roller, etc., the resin component is dissolved in the organic solvent without residue.

[0054] In premixing, the binder prepared by the binder blending is mixed with the metal component. In premixing, the binder and the metal powder are mixed and fused using a mixer or a crusher. Since the metal powder is sometimes not mixed and remains, the mixing is performed until there is no lumps of the metal powder by visual observation. Since sufficient mixing and stirring are not performed in the premixing, if left standing, the binder and the metal component may be separated. Therefore, mixing is performed quickly after premixing.

[0055] In the kneading, the mixture of the pre-mixed binder and the metal powder is paste-formed. The pre-mixed mixture is placed in a sealed kneading container with a lid made of polyethylene or polypropylene. The mixture placed in the kneading container is kneaded by rotating it using a self-revolution device. As the self-revolution device, the SK series of Shashin Chemical Co., Ltd. or the ARE series of THINKY Co., Ltd. can be listed.

[0056] In the kneading process, the mixture is deaerated and stirred to form a paste. It is preferred to set an auto-revolution condition suitable for deaeration, stirring and pasting, and divide the steps into primary kneading, secondary kneading, and tertiary kneading, so as to efficiently perform kneading.

[0057] In the first kneading, the degassing of the mixture is promoted by performing kneading that is substantially only revolution. In order to perform sufficient degassing, the centrifugal acceleration of the first kneading is preferably 80% or more of the centrifugal acceleration of the third kneading required for paste formation. The time of the first kneading is preferably 10% or more of the total kneading time. If it is the first kneading of the mixture composed of the above-mentioned metal powder and binder, the centrifugal acceleration is preferably 80G or more and the kneading time is preferably 45 seconds or more.

[0058] The second kneading is continued without a time interval from the first kneading. In the second kneading, in addition to the revolution, the rotation is also performed. Thus, the stirring of the defoamed mixture is promoted by rotation. Since the purpose of the second kneading is to stir the mixture as a whole, the kneading is carried out by the revolution with a rotation speed less than that of the first kneading and the rotation with a rotation speed less than that of the revolution. In order to carry out sufficient stirring, the centrifugal acceleration of the second kneading is preferably more than 50% of the centrifugal acceleration of the third kneading. The time of the second kneading is preferably more than 10% of the overall kneading time. If it is the second kneading of the mixture composed of the above-mentioned metal powder and the binder, it is preferred that the centrifugal acceleration is more than 65G and the kneading time is more than 45 seconds.

[0059] The 3rd kneading is continued without separating the time from the 2nd kneading. In the 3rd kneading, a larger revolution and rotation are applied to the kneaded material stirred by the 2nd kneading, and the mixture is greatly stirred. The stirring with a rotation speed greater than the revolution of the 2nd kneading and the rotation speed less than the revolution is performed to apply shear force to the mixture. The stirring by applying shear force promotes the paste-forming of the mixture. The force applied to the mixture by the 3rd kneading is preferably greater than that of the 1st kneading and the 2nd kneading. That is, the centrifugal acceleration in the 3rd kneading is preferably greater than that of the 1st kneading and the 2nd kneading. If it is the 3rd kneading of the mixture composed of the above-mentioned metal powder and the binder, the centrifugal acceleration is preferably above 100G and the kneading time is above 250 seconds.

[0060] The active metal paste completed by kneading is printed on the ceramic substrate. The active metal paste is printed with a uniform thickness by screen printing or the like. The printing thickness of the paste is preferably 15 to 40 μm. In the case of a ceramic circuit substrate with metal circuits on both sides, after the active metal paste is printed on one side, the paste is dried by heating in the atmosphere. Thereafter, the active metal paste is printed on the other side, and the paste is dried in the same manner.

[0061] Next, a metal plate is placed on the ceramic substrate after the active metal paste is printed and dried. When the metal plate is a copper plate or a copper alloy plate, the ceramic substrate with the metal plate is heated at 700 to 900°C to bond the ceramic substrate to the metal plate. The heating step is performed in a vacuum or a non-oxidizing atmosphere as required. When performed in a vacuum, the pressure is preferably 1×10 -2 Pa or less. Examples of the non-oxidizing atmosphere include a nitrogen atmosphere and an argon atmosphere. The active metal paste melts and solidifies by performing heat bonding. The active metal paste functions as a bonding layer that bonds the ceramic substrate and the metal plate.

[0062] When the metal plate is processed into a circuit shape in advance, a ceramic circuit substrate can be obtained by bonding the processed metal circuit to the ceramic substrate. When a metal plate that has not been processed into a circuit shape is bonded to a ceramic substrate, the metal circuit is formed by etching or the like. Not only the metal plate but also the bonding layer can be processed into a circuit shape by etching.

[0063] Through the above-mentioned process, a ceramic circuit substrate can be manufactured. Next, a process of bonding a semiconductor element and the ceramic circuit substrate is performed. A bonding layer is provided at the portion where the semiconductor element is bonded. The bonding layer preferably contains solder or brazing material. A semiconductor element is provided thereon via the bonding layer. A wire bonding portion may also be provided as required. Multiple semiconductor elements and multiple wire bonding portions may also be provided as required.

[0064] According to an embodiment of the present invention, an active metal paste with more uniformly dispersed components and fewer bubbles can be obtained. In particular, active metals are chemically active and highly reactive. Therefore, it is preferred to efficiently and uniformly disperse them in the paste in a shorter time. According to an embodiment of the present invention, through a kneading process, the components of the metal powder containing the active metal can be more uniformly dispersed in the paste in a shorter time.

[0065] According to an embodiment of the present invention, an active metal paste can be manufactured in which the dispersibility of the copper element and the active metal element is respectively lower than 1.0. The dispersibility of each of the copper element and the active metal element is lower than 1.0, which means that the copper element and the active metal element are fully dispersed in the active metal paste. By making the dispersibility of each of the copper element and the active metal element lower than 1.0, aggregation can be suppressed and the fluidity of the paste is improved. Therefore, it becomes easy to print the active metal paste. In addition, since each particle can easily enter between other particles, the reaction is effectively carried out and the bonding property is improved.

[0066] (Examples 1 to 12, Comparative Examples 1 to 10)

[0067] Prepare the ceramic substrates shown in Table 1. The ceramic substrate is a silicon nitride substrate or an aluminum nitride substrate. The thermal conductivity of the silicon nitride substrate is 90 W / (m·K), and the three-point bending strength is 650 MPa. The thermal conductivity of the aluminum nitride substrate is 170 W / (m·K), and the three-point bending strength is 300 MPa. The size of the ceramic substrate is 30 mm in length and 50 mm in width. The thickness of the silicon nitride substrate is 0.32 mm, and the thickness of the aluminum nitride substrate is 0.635 mm. In Table 1, the silicon nitride substrate is recorded as Si3N4, and the aluminum nitride substrate is recorded as AlN.

[0068] Next, the metal components of the paste shown in Table 1, i.e., metal powders, are prepared. The metal powder is a silver-based powder (Ag-Cu-Sn-Ti) or a copper-based powder (Cu-Sn-TiH). The ratio of each metal component in the silver-based powder is 58 mass % for Ag, 30 mass % for Cu, 10 mass % for Sn, and 2 mass % for Ti. The ratio of each metal component in the copper-based powder is 68 mass % for Cu, 20 mass % for Sn, and 12 mass % for TiH. The average particle size of the Ag powder is 2 μm. The average particle size of the Cu powder is 1 μm. The average particle size of the Sn powder is 5 μm. The average particle size of the Ti powder is 5 μm. The average particle size of the TiH powder is 6 μm.

[0069] Next, an adhesive was prepared by placing 7% by mass of ethyl cellulose, 3% by mass of sarcosinate, and 90% by mass of terpineol in a polyethylene wide-mouth bottle with a lid, and rotating the bottle with a can-type drum for 24 hours to prepare an adhesive.

[0070] Next, the metal powder and the binder were premixed. 20% by mass of the binder was placed in a polyethylene cylindrical container relative to a total of 100% by mass of the metal powder. The stirring blade was fixed in a vertical direction relative to the opening of the cylindrical container, and the cylindrical container was rotated at 50 rpm for 3 minutes to premix and prepare a mixture of the metal powder and the binder.

[0071] Next, the mixture of the premixed binder and the metal powder was kneaded to form a paste. A sealed lid was installed on the polyethylene cylindrical container with the premixed mixture, and the first, second and third kneading were performed using a kneading device. The kneading device used was SK-3000 manufactured by Shashin Chemical. The kneading conditions of the rotational speed (rpm), rotational speed (rpm), centrifugal acceleration (G) and kneading time (seconds) in each step are shown in Tables 1 and 2.

[0072]

[0073]

[0074] Table 1 shows the ratio (G1 / G3) of the centrifugal acceleration of the first kneading (G1) to the centrifugal acceleration of the third kneading (G3), and the ratio (T1 / T1-3) of the first kneading time (T1-3=T1+T2+T3). Table 2 shows the ratio (G2 / G3) of the centrifugal acceleration of the second kneading (G2) to the centrifugal acceleration of the third kneading (G3), and the ratio (T2 / T1-3) of the second kneading time (T2) to the total kneading time (T1-3).

[0075] Regarding the kneading conditions of the paste in Examples 1 to 12, the ratio of the centrifugal acceleration of the first kneading to the centrifugal acceleration of the third kneading (G1 / G3) and the ratio of the first kneading time to the total kneading time (T1 / T1 to 3) were within the preferred range. The ratio of the centrifugal acceleration of the second kneading to the centrifugal acceleration of the third kneading (G2 / G3) and the ratio of the second kneading time to the total kneading time (T2 / T1 to 3) were within the preferred range. On the other hand, in Comparative Examples 1 to 10, these values ​​were outside the preferred range.

[0076] Next, in order to confirm the cohesion of the metal powder in the paste, the maximum coagulation particle size is measured using a fineness meter. The fineness meter is a metal measuring tool with a groove with an inclined bottom engraved on its surface. The depth of one end of the groove is zero. The paste is placed in the deeper part of the groove, and the maximum coagulation particle size can be easily measured by applying the paste from the deep side to the shallow side with a metallic scraper. The case where the maximum coagulation particle size measured by the fineness meter is less than 10μm is defined as a paste without large coagulation. In Table 3, the example where the maximum coagulation particle size measured is less than 10μm is recorded as "OK", and the example where the maximum coagulation particle size measured is greater than 10μm is recorded as "NG".

[0077] The active metal paste completed by kneading is printed onto a ceramic substrate. Use a screen plate with a size of 320mm×320mm and a mesh size of 200μm to print the active metal paste. First, print three rectangular circuit shapes on one side (upper surface) of the ceramic substrate. Dry the active metal paste printed on one side by heating at 100°C in the atmosphere for 1 minute. Then, print a rectangular circuit shape on the other side (lower surface). Dry the active metal paste printed on the other side by heating at 100°C in the atmosphere for 1 minute.

[0078] Next, in order to confirm the dispersion of the metal powder in the paste after printing and drying, the dispersibility of the Cu particles and the dispersibility of the active metal particles are evaluated. The paste is printed on a polyethylene terephthalate (PET) film under the same conditions as the ceramic substrate and dried. The flat surface of the paste on the membrane side is observed using an energy dispersive X-ray analyzer (SEM-EDX). SEM-EDX uses S-5500 manufactured by Hitachi High-Technologies or an equivalent device. The size of the observation area is set to 100μm×80μm. The mapping data of the Cu element and the mapping data of the active metal element present in the observation area are obtained. From the mapping data of the Cu element, the particle size distribution is calculated by particle size analysis software. That is, the mapping data of the Cu element is subjected to Voronoi segmentation. The divided area distribution is measured, and the average and standard deviation of the area are calculated. The value obtained by dividing the standard deviation by the average value is calculated as the dispersibility (standard deviation / average value). For active metal elements, the particle size distribution is calculated by the mapping data of the active metal elements using particle size analysis software. The divided area distribution is measured, and the average value and standard deviation of the area are calculated. The value obtained by dividing the standard deviation by the average value is calculated as the dispersion (standard deviation / average value). ImageJ can be used for particle size analysis software.

[0079] Next, oxygen-free copper plates with a length of 30 mm × a width of 50 mm × a thickness of 0.8 mm were placed on both sides of the ceramic substrate after the paste was printed and dried, and heated to bond. When using silver paste (Ag-Cu-Sn-Ti), the bonding temperature was set to 820°C. When using copper paste (Cu-Sn-TiH), the bonding temperature was set to 600°C. The bonding time was set to 10 minutes in each case, and the temperature was kept constant in a vacuum (1×10 -2 Pa or less) for bonding.

[0080] Next, the oxygen-free copper plate bonded to the ceramic substrate was etched. Through etching, metal circuits were formed at three locations on the surface of the ceramic substrate and at one location on the back. For the circuit shapes at the three locations on the surface, a 5 mm pull back was formed from the periphery of the ceramic substrate, and a 5 mm non-circuit portion was also formed between the circuit shapes. For the circuit shape on the back, a 5 mm pull back was formed from the periphery of the ceramic substrate.

[0081] Next, in order to confirm the microscopic bonding between the metal circuit and the ceramic substrate using the paste, the gap of the bonding layer of the surface circuit was measured by ultrasonic flaw detection (SAT: Scanning Acoustic Tomograph). The case where a defect with a diameter of 1 mm or more was observed was judged as a poor gap. In Table 3, the case where it was not judged as a poor gap was recorded as "OK", and the case where it was judged as a poor gap was recorded as "NG".

[0082] Next, in order to confirm the macroscopic bonding between the metal circuit and the ceramic substrate using the paste, the peel strength was measured as the bonding strength between the metal circuit and the ceramic substrate. The peel strength was measured by fixing the ceramic circuit substrate on a fixture and peeling off a part of the upper surface metal circuit at 50 mm / min in the vertical direction. The respective measurement results are shown in Table 3.

[0083] Table 3

[0084]

[0085] The pastes of Examples 1 to 12 had no poor aggregation and the dispersibility values ​​were within the preferred range. This is considered to be because the generation of bubbles, aggregation, etc. in the paste was suppressed by setting the kneading conditions of the paste within the preferred range. In contrast, poor aggregation was observed in Comparative Examples 1 to 10 and the dispersibility values ​​were out of the preferred range. This is considered to be because bubbles, aggregation, etc. were not eliminated and remained in the paste.

[0086] In addition, for the ceramic circuit substrates involved in Examples 1 to 12, there was no void defect, and the value of the bonding strength was within the preferred range. It is believed that this is because the ceramic and the metal circuit were bonded using a paste with less bubbles and aggregation. In contrast, for Comparative Examples 1 to 10, void defects were observed, and the value of the bonding strength was out of the preferred range. It is believed that this is because the ceramic and the metal circuit were bonded using a paste with more bubbles and aggregation, resulting in more bonding defects.

[0087] As described above, the ceramic circuit board according to the embodiment has few bonding defects and high bonding strength, and is therefore most suitable for a semiconductor device having a semiconductor element mounted thereon.

[0088] The embodiments of the present invention include the following features.

[0089] (Feature 1)

[0090] A method for producing an active metal paste, comprising the steps of: mixing a binder obtained by dissolving a resin in an organic solvent with metal powders containing copper and an active metal to produce a mixture containing 60 to 95% by mass of the metal powders; and

[0091] A kneading step of subjecting the mixture to rotation and revolution to generate an active metal paste.

[0092] (Feature 2)

[0093] The method for producing an active metal paste according to feature 1, wherein the kneading step includes a first kneading step of kneading by revolution, a second kneading step of kneading by revolution and rotation after the first kneading, and a third kneading step of kneading by revolution and rotation after the second kneading.

[0094] The revolution speed in the second kneading is lower than the revolution speed in the first kneading.

[0095] The rotation speed of the above-mentioned rotation in the above-mentioned second kneading is lower than the rotation speed of the above-mentioned revolution in the above-mentioned second kneading,

[0096] The rotation speed of the revolution in the three times of kneading is greater than the rotation speed of the revolution in the two times of kneading.

[0097] The rotation speed of the autorotation in the three kneadings is lower than the rotation speed of the revolution in the three kneadings.

[0098] (Feature 3)

[0099] According to the method for manufacturing an active metal paste described in Feature 2, in the above-mentioned mixing step, the centrifugal acceleration of the above-mentioned first mixing is more than 80% of the centrifugal acceleration of the above-mentioned third mixing, and the centrifugal acceleration of the above-mentioned second mixing is more than 50% of the centrifugal acceleration of the above-mentioned third mixing.

[0100] (Feature 4)

[0101] The method for producing an active metal paste according to feature 2 or feature 3, wherein in the kneading step, the first kneading time and the second kneading time are each 10% or more of the total kneading time.

[0102] (Feature 5)

[0103] A method for producing a ceramic circuit board, comprising the steps of: performing the method for producing an active metal paste according to any one of features 1 to 4; and

[0104] A joining step of joining a metal member to a ceramic substrate via the active metal paste.

[0105] (Feature 6)

[0106] A method for manufacturing a semiconductor device, comprising the following steps: a step of performing the method for manufacturing an active metal paste according to any one of features 1 to 4;

[0107] a step of bonding a metal member to a ceramic substrate via the active metal paste; and

[0108] A mounting step of mounting a semiconductor element on the metal member having the circuit formed thereon.

[0109] (Feature 7)

[0110] An active metal paste, characterized in that, in the active metal paste containing copper and at least one active metal, the dispersibility of the copper element and the active metal element are respectively less than 1.0.

[0111] (Feature 8)

[0112] The active metal paste according to feature 7, wherein, in the inorganic component, the copper content is 50 mass % or more, the active metal content is 4 mass % or more and 30 mass % or less, the content of one or two selected from tin or indium is 5 mass % or more and 45 mass % or less, and the carbon content is 0 mass % or more and 2 mass % or less.

[0113] (Feature 9)

[0114] The active metal paste according to feature 7, wherein, in the inorganic component, the silver content is greater than 20 mass % and less than 60 mass %, the copper content is greater than 15 mass % and less than 40 mass %, the active metal content is greater than 1 mass % and less than 15 mass %, and the content of one or two selected from tin or indium is greater than 5 mass % and less than 25 mass %.

[0115] (Feature 10)

[0116] A ceramic circuit substrate, comprising:

[0117] Ceramic substrates, and

[0118] A metal circuit bonded to the ceramic substrate via a bonding layer formed of the active metal paste according to any one of Features 7 to 9.

[0119] (Feature 11)

[0120] The ceramic circuit substrate according to feature 10, wherein the ceramic substrate is any one of an aluminum oxide substrate, an aluminum nitride substrate, and a silicon nitride substrate.

[0121] (Feature 12)

[0122] A ceramic circuit substrate according to feature 11, wherein the metal circuit is made of copper or a copper alloy.

[0123] (Feature 13)

[0124] A semiconductor device comprising:

[0125] The ceramic circuit substrate according to any one of features 10 to 12, and

[0126] A semiconductor element mounted on the above-mentioned metal circuit via a bonding layer.

[0127] Several embodiments of the present invention are illustrated above, but these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other ways, and various omissions, substitutions, changes, etc. can be made without departing from the scope of the main purpose of the invention. These embodiments and their modifications are included in the scope and main purpose of the invention, and are also included in the invention recorded in the claims and their equivalents. In addition, the above-mentioned embodiments can be implemented in combination with each other.

[0128] Explanation of symbols

[0129] 1…Ceramic circuit substrate

[0130] 2…Ceramic substrate

[0131] 3…Metal Circuit

[0132] 4…Joint layer

[0133] 5…Mixing container

[0134] 6…Active Metal Paste

[0135] 7…Metal Plate

[0136] 8…Joint layer

[0137] 9…Semiconductor components

[0138] 10…Semiconductor devices

[0139] 11…Wire bonding part

[0140] 12…Lead frame

[0141] 13…Molding resin

Claims

1. A method for producing an active metal paste, comprising the following steps: A pre-mixing step of mixing a binder obtained by dissolving a resin in an organic solvent with a metal powder containing copper and an active metal to produce a mixture containing 60 to 95% by mass of the metal powder; and A kneading step of subjecting the mixture to rotation and revolution to generate an active metal paste.

2. The method for producing an active metal paste according to claim 1, wherein: The kneading step includes a first kneading step of kneading by revolution, a second kneading step of kneading by revolution and rotation after the first kneading, and a third kneading step of kneading by revolution and rotation after the second kneading. The revolution speed in the second kneading is smaller than the revolution speed in the first kneading, The rotation speed of the autorotation in the second kneading is lower than the revolution speed in the second kneading, The revolution speed in the third kneading is greater than the revolution speed in the second kneading, The rotation speed of the autorotation in the three kneadings is lower than the rotation speed of the revolution in the three kneadings.

3. The method for producing an active metal paste according to claim 2, wherein: In the kneading step, the centrifugal acceleration of the first kneading is 80% or more of the centrifugal acceleration of the third kneading, and the centrifugal acceleration of the second kneading is 50% or more of the centrifugal acceleration of the third kneading.

4. The method for producing an active metal paste according to claim 2, wherein: In the kneading step, the time for the first kneading and the time for the second kneading are each 10% or more of the total kneading time.

5. A method for manufacturing a ceramic circuit substrate, comprising: A step of performing the method for producing an active metal paste according to any one of claims 1 to 4; and A joining step of joining a metal member to a ceramic substrate via the active metal paste.

6. A method for manufacturing a semiconductor device, comprising: A step of performing the method for producing an active metal paste according to any one of claims 1 to 4; a step of bonding a metal member to a ceramic substrate via the active metal paste; and A mounting step of mounting a semiconductor element on the metal member having the circuit formed thereon.

7. An active metal paste, characterized in that: In the active metal paste including copper and at least one active metal, the dispersibility of the copper element and the active metal element are each less than 1.

0.

8. The active metal paste according to claim 7, wherein In the inorganic components, the content of copper is 50 mass % or more, the content of active metal is 4 mass % or more and 30 mass % or less, the content of one or two selected from tin or indium is 5 mass % or more and 45 mass % or less, and the content of carbon is 0 mass % or more and 2 mass % or less.

9. The active metal paste according to claim 7, wherein Among the inorganic components, the content of silver is greater than 20 mass % and less than 60 mass %, the content of copper is greater than 15 mass % and less than 40 mass %, the content of active metal is greater than 1 mass % and less than 15 mass %, and the content of one or two selected from tin or indium is greater than 5 mass % and less than 25 mass %.

10. A ceramic circuit substrate comprising: Ceramic substrates, and A metal circuit bonded to the ceramic substrate via a bonding layer formed of the active metal paste according to any one of claims 8 to 9.

11. The ceramic circuit substrate according to claim 10, wherein: The ceramic substrate is any one of an aluminum oxide substrate, an aluminum nitride substrate and a silicon nitride substrate.

12. The ceramic circuit substrate according to claim 11, wherein: The metal circuit is made of copper or a copper alloy.

13. A semiconductor device comprising: The ceramic circuit substrate according to claim 12, and A semiconductor element is mounted on the metal circuit via a bonding layer.

Citation Information

Patent Citations

  • Binding material, binding body, and binding method

    WO2012070262A1

  • Bonded body, ceramic circuit board using same, and semiconductor device

    WO2022085654A1